Policy misrecognitions and paradoxes: Developing more contextually attuned access and equity policies in Australian higher education. Issue 8 (November 2019) - Bennett, Anna; Lumb, Matt
In this paper we discuss recent policy attempts (in 2017) to introduce new frameworks for Australian higher education access and equity programs. These include introducing fees and a tendering process for access or 'enabling' programs, as they are called in Australia, and an evaluation framework based on an evidence hierarchy for widening participation or 'equity' programs. We illuminate how those policymaking attempts contradict the conditions required for equity-oriented programs because they misrecognise the experiences of the participants. We argue that different conceptual approaches to provision and evaluation are required for practitioners, providers and policymakers to shape future policy together (Heimans and Singh, 2018 ) so that enabling and equity programs can be understood in ways that value the knowledges and experiences of the participants involved (Sayer, 2011 ). Our aim is to contribute to work that disrupts the positioning of 'objective' policy evaluation frameworks vs 'subjective' practices because this decontextualises (Burke and Lumb, 2018 ) and oversimplifies (Tesar, 2016a ), and may serve paradoxically to reduce the programs' impacts.